2006
DOI: 10.1016/j.actatropica.2006.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic markers for the identification and characterization of Opisthorchis viverrini, a medically important food borne trematode in Southeast Asia

Abstract: The liver fluke, Opisthorchis viverrini, is one of the major food borne trematodes in Southeast Asia, where infection causes hepatobiliary disease and subsequent development of cholangiocarcinoma. In Thailand, O. viverrini is most prevalent in the northeast where there is marked regional variation in the rate of infection in humans at provincial, district and village levels. To date, the roles of genetic variation of O. viverrini on this observed variability in infection, transmission and associated disease ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 12 publications
(30 reference statements)
0
17
2
Order By: Relevance
“…Comparison of the RAPD profiles revealed that O. viverrini from Lao PDR was genetically distinct from those collected in Thailand ). This finding was supported by allozyme electrophoresis analyses using 32 enzyme loci as genetic markers to examine systematics and population structure of O. viverrini (Saijuntha et al 2006a;b;Saijuntha et al 2007). O. viverrini from 15 different localities in Thailand and Lao PDR were analyzed with 32 enzyme loci.…”
Section: Introductionmentioning
confidence: 73%
“…Comparison of the RAPD profiles revealed that O. viverrini from Lao PDR was genetically distinct from those collected in Thailand ). This finding was supported by allozyme electrophoresis analyses using 32 enzyme loci as genetic markers to examine systematics and population structure of O. viverrini (Saijuntha et al 2006a;b;Saijuntha et al 2007). O. viverrini from 15 different localities in Thailand and Lao PDR were analyzed with 32 enzyme loci.…”
Section: Introductionmentioning
confidence: 73%
“…Based on our previous MEE studies to define a sufficient number of enzyme loci to genetically characterise O. viverrini (Saijuntha et al, 2006a,b) 28 enzymes encoding a presumptive 32 loci were used herein for the genetic characterization of O. viverrini . This number of enzyme loci is considerably more than that employed in MEE studies on other species of food-borne trematodes (Agatsuma et al, 1986; 1994; Park et al, 2002) and provides the opportunity to assess the significance of genetic variation detected among geographical localities, and to define a sufficient number of independent genetic markers for biological and epidemiological studies.…”
Section: Resultsmentioning
confidence: 99%
“…Five polymorphic enzymes, ENOL, FDP, PGAM, PGM and TPI, all of which are known to be polymorphic in O. viverrini from Thailand (Saijuntha et al 2006;Saijuntha et al 2007), were examined in samples from populations of the O. viverrini species from Lao PDR.…”
Section: Discussionmentioning
confidence: 99%
“…Supernatants were removed directly by loading pen from each well and loaded onto the cellulose acetate gel (Cellogel; Milan) as the support medium. Each gel was stained histochemically for a specific enzyme as described for the five enzymes that were previously shown to be polymorphic (Saijuntha et al 2006;Saijuntha et al 2007). The polymorphic enzymes used for the population genetic study in Thailand were used for in the present study for O. viverrini from Lao PDR, namely: enolase (ENOL, EC 4.2.1.11), fructose-1,6-diphosphatase (FDP, 3.1.3.11), phosphoglycerate mutase (PGAM, 2.7.5.3), phosphoglucomutase (PGM, EC 2.7.5.1), and triose phosphate isomerase (TPI, EC 5.3.1.1).…”
Section: Multilocus Enzyme Electrophoresismentioning
confidence: 99%